Compliance of thyroid nodules through ultrasound-guided trucut/core needle biopsy with Thyroid imaging, reporting, and data system score and surgical pathology - Ahmed M. Hassan; Ahmed Abd Elrady Ahmed; Radwa Nabawy Abd Allah Abd El Wahab; Noha M. Nagla (Al-Azhar Assiut Medical Journal)
Background and Aim The ultrasound-guided trucut/core needle biopsy (CNB) has been effectively used as a supplemental approach for the assessment of thyroid nodules. We aimed to evaluate the diagnostic value of the ultrasound-guided trucut needle biopsy of thyroid nodules in correlation with Thyroid imaging, reporting, and data system (TIRADS score). Patient and methods Between November 2020 and November 2021, this prospective study had been carried out at Al-Azhar University Hospital, Assiut, in the department of general surgery and diagnostic and interventional radiology. There were 50 patients in this study, All of them had clinically suspected thyroid nodules. Results The mean age of patients involved in the current research was 43.9±11.7 years. Females represented 92% of the study groups, while males made up just 8%. There was no considerable variation in the prevalence of diabetes mellitus (DM) or hypertension among the study groups. The most prevalent diagnosis in the normocalcemic group (39.63%) was simple goiter, while in the hypocalcemic group was malignancy (44.44%). In terms of preoperative diagnosis, there was a substantial diversity among the 2 groups. Conclusion Thyroid CNB used as an alternative choice for cases with a previous non-diagnostic or indeterminate diagnosis, but is presently being recommended as a first-line method for identification of thyroid nodules in selected cases. Accuracy of CNB in thyroid nodules is high with low rate of drastic effects.